Effect of Potassium on the Mechanisms of Biomass Pyrolysis Studied using Complementary Analytical Techniques. Issue 8 (15th March 2016) - Le Brech, Yann; Ghislain, Thierry; Leclerc, Sébastien; Bouroukba, Mohammed; Delmotte, Luc; Brosse, Nicolas; Snape, Colin; Chaimbault, Patrick; Dufour, Anthony
Abstract: Complementary analytical methods have been used to study the effect of potassium on the pyrolysis mechanisms of cellulose and lignocellulosic biomasses. Thermogravimetry, calorimetry, high‐temperature 1 H NMR spectroscopy (in situ and real‐time analysis of the fluid phase formed during pyrolysis), and water extraction of quenched char followed by size‐exclusion chromatography coupled with mass spectrometry have been combined. Potassium impregnated in cellulose suppresses the formation of anhydrosugars, reduces the formation of mobile protons, and gives rise to a mainly exothermic signal. The evolution of mobile protons formed from K‐impregnated cellulose has a very similar pattern to the evolution of the mass loss rate. This methodology has been also applied to analyze miscanthus, demineralized miscanthus, miscanthus re‐impregnated with potassium after demineralization, raw oak, and Douglas fir. Hydrogen mobility and transfer are of high importance in the mechanisms of biomass pyrolysis. Abstract : Potassium gets intimate with biomass ! Complementary analytical methods have been developed to study the effect of potassium on the pyrolysis mechanisms of biomass. Thermogravimetry, calorimetry, in situ 1 H NMR spectroscopy, and size‐exclusion chromatography coupled with mass spectrometry have been combined for the first time.